Racial and ethnic disparities in colorectal cancer incidence and mortality - Carethers, John M. (Advances in cancer research, 2021)
The occurrence of colorectal cancer (CRC) shows a large disparity among recognized races and ethnicities in the U.S., with Black Americans demonstrating the highest incidence and mortality from this disease. Contributors for the observed CRC disparity appear to be multifactorial and consequential that may be initiated by structured societal issues (e.g., low socioeconomic status and lack of adequate health insurance) that facilitate abnormal environmental factors (through use of tobacco and alcohol, and poor diet composition that modifies one's metabolism, microbiome and local immune microenvironment) and trigger cancer-specific immune and genetic changes (e.g., localized inflammation and somatic driver gene mutations). Mitigating the disparity by prevention through CRC screening has been demonstrated; this has not been adequately shown once CRC has developed. Acquiring additional knowledge into the science behind the observed disparity will inform approaches towards abating both the incidence and mortality of CRC between U.S. racial and ethnic groups.